The comparison of cephalometric steiner’s skeletal analysis (SNA, SNB, ANB) in different ethnicity: Komparasi nilai sefalometri analisis skeletal Steiner (SNA, SNB, ANB) pada berbagai etnis - Widjaja, Nadia S.; Pawinru, Ardiansyah S. (Makassar Dental Journal PDGI Makassar, 2025)
Cephalometric analysis plays an important role in planning corrective treatment and assessing changes that occur during orthodontic treatment. One of the most commonly used cephalometric analyses is the Steiner analysis, which is used to determine the anteroposterior position of the maxilla and mandible, particularly the SNA, SNB, and ANB angles. Longitudinal studies conducted between 1940 and 1960 serve as the commonly used standard of normality and function as the baseline for evaluation. However, the morphological variations between different ethnic groups and populations cannot be ignored and should be considered when determining cephalometric normalcy standards for various racial and ethnic groups. To address this issue, some researchers have attempted to define cephalometric values for different ethnic groups to provide a more comprehensive approach. This study compares the standard cephalometric values of Steiner analysis (SNA, SNB, ANB) across different ethnic groups. It was concluded that there are specific standard cephalometric values for each ethnic group, making them highly useful for diagnosis and developing treatment plans.